top of page
Search

# 3 Algebraic Rules Of Expansion

Updated: Jun 16, 2021

(a+b)² = a²+2ab+b²

(a-b)² = a²-2ab+b²

(a+b)(a-b) = a²-b²

@mathlobbymotivation

The three algebraic rules of expansion are the core of Algebra. We will be using them regularly in all levels of Secondary Math.

Also, the three algebraic rules of expansion are widely tested in O Level and N Level Math Examinations too. Hence, Math Lobby will be teaching you how to apply these 3 algebraic rules today.

### Rule 1: (a+b)² = a²+2ab+b²

Question: Expand (2x+4)²

(2x+4)²

= (2x)²+2(2x)(4)+4²

= 4x²+16x+16

Math Lobby Tips:

- Let 2x be a and 4 be b

- Substitute into Rule 1: (a+b)² = a²+2ab+b²

- Question solved!

### Rule 2: (a-b)² = a²-2ab+b²

Question: Expand (3x-2)²

(3x-2)²

= (3x)²-2(3x)(2)+2²

= 9x²-12x+4

Math Lobby Tips:

- Let 3x be a and 2 be b

- Substitute into Rule 2: (a-b)² = a²-2ab+b²

- Question solved!

### Rule 3: (a+b)(a-b) = a²-b²

Question: Expand 25x²-16y²

25x²-16y²

= (5x+4)(5x-4)

Math Lobby Tip:

- Let √25 be a and √16 be b

- Substitute into Rule 3: (a+b)(a-b) = a²-b²

- Question solved!

If you want to receive daily Secondary Math Tips from us,

FOLLOW our Instagram page at https://www.instagram.com/mathlobbymotivation/